Surface charge compensation and ferroelectric domain structure of triglycine sulfate revealed by voltage-modulated scanning force microscopy - V. Likodimos; Labardi, M.; Allegrini, M.; Garcia, N.; Osipov, V.V. (Surface Science, 2001)
The interplay between surface morphology and ferroelectric domain structure on triglycine sulfate (TGS) (010) cleavage faces is investigated by voltage-modulated scanning force microscopy in the dynamic contact mode. A resonance enhancement method is exploited to increase imaging contrast and sensitivity to slight variations of surface polarity. Evidence of electric contrast of the structural nuclei forming due to surface reconstruction of the TGS cleavage face, is provided, further supported by second harmonic measurements. Lateral growth at ambient conditions and high mobility of the surface nuclei relative to the spontaneous ferroelectric domain motion after cooling from above Tc is detected. Surface charge screening by the conductive liquid film that condenses on the cleavage surface and its interface dynamics are suggested to determine the kinetics of surface nuclei during ferroelectric domain coarsening and the formation of a zig-zag domain boundary. © 2001 Elsevier Science B.V. All rights reserved.